Opisthopus transversus Rathbun 1893 - Campos, Ernesto (Zenodo, 2016)
Opisthopus transversus Rathbun, 1893 (Figs. 3 F–I, 4A–D) Material examined and new hosts. 1 female, Nov. 2014, from commercial catches, Ensenada shellfish market, collected in Punta Colonet, Ensenada, Baja California, Mexico (30°57'43.65"N, 116°19'22.44"W) in Tivela stultorum . Distribution. Santa Cruz, California, U.S. A to Laguna de San Ignacio, Baja California Sur, Mexico (Campos & Manning 2000). Hosts. Symbiont in the giant Pacific chiton Cryptochiton stelleri (von Middendorff, 1847); the gastropods Aplysia vaccaria Winkler, 1955, Bulla gouldiana Pilsbry, 1895, Conus californicus Reeve, 1844, Lithopoma undosum (Wood, 1828) [= Megastraea undosa (W. Wood)], Megathura crenulata (Sowerby I, 1825), Navanax inermis (J. G. Cooper, 1862), and Neverita lewisii (Gould, 1847); the bivalves Atrina tuberculosa (G. B. Sowerby I, 1835), Crassadoma gigantea (J.E. Gray, 1825), Crassostrea gigas (Thunberg, 1793), Megapitaria squalida (G. B. Sowerby I, 1835), Modiolus capax , Modiolus sp., Mytilus edulis (see below), Nuttallia nuttallii , Pholas sp., Platyodon sp., Pseudochama exogyra (Conrad, 1837), Tivela stultorum , Tresus nuttallii , Zirfaea sp., and Zirfaea pilsbryi Lowe, 1931. Also commensal in the tube of the polychaete Chaetopterus variopedatus (Renier, 1804), and the cloaca of the holothuroids Apostichopus californicus (Stimpson, 1857), A. parvimensis (Clark, 1913), and Molpadia arenicola (Stimpson, 1857), (Schmitt et al. 1975; Garth & Abbott 1980; Ricketts et al . 1980; Campos et al. 1992). Other hosts. Garth & Abbott (1980) recorded the species in the Atlantic bivalve Dinocardium robustum (Lightfoot, 1786), but the presence of this bivalve in the eastern Pacific should be confirmed. Likewise, the record of Mytilus edulis needs confirmation since this species is validly reported only from embayments in California U.S.A. Mytilids from open coastal area may belong to M. galloprovincialis or M. trossulus . Remarks. According to Hopkins & Scanland (1964) the occurrence of O. transversus in multiple host species is evidence of the non-specificity of this pinnotherid. Although this conclusion is evident, another interpretation is that the species needs more than one host to complete its life history. The generalist behavior along the life history of O. transversus probably involves a complex relationship with their invertebrate hosts. Host selection is most probably not by chance. Thus, following Hopkins & Scanland (1964) it is possible to hypothesize that young individuals of Opisthopus infest a temporary host like the giant Pacific chiton Cryptochiton , moving initially to one or several larger hosts, e.g. Lithopoma , Megathura , or Stichopus , followed by a final selection of a definitive host, e.g. Crassadoma , Molpadia , or Zirfaea in which crab grow until they reach the adult phase, including ovigerous females. I concur with Hopkins & Scanland (1964) that host selection may be linked to host size, which provides space for growth and shelter; however, different hosts may also provide different types of nutrients necessary for development and reproduction. Because O. transversus was recorded in the Gulf of California (Glassell 1935a), for the past 20 years I have examined potential hosts in beaches around San Felipe, Puertecitos, and Bahía de Los Angeles, Gulf of California, Mexico, including species of Mytilidae, Veneridae, Solecurtidae, Cardidae, and Hiatellidae, but no pinnotherid assignable to this species have been collected. The juvenile males recorded by Glassell, which were unavailable for study, may belong to Pinnaxodes gigas Green, 1992, a species that morphologically resemble O. transversus and inhabits the Gulf of California (see below). : Published as part of Campos, Ernesto, 2016, The Pinnotheridae of the northeastern Pacific (Alaska to Mexico): zoogeographical remarks and new bivalve hosts (Crustacea, Brachyura, Pinnotheridae), pp. 311-329 in Zootaxa 4170 (2) on pages 317-320, DOI: 10.11646/zootaxa.4170.2.5, http://zenodo.org/record/265679 : {"references": ["Campos, E. & Manning, R. B. (2000) The identities of Pinnotheres nudus Holmes, 1895 and P. nudus sensu Weymouth, 1910 (Crustacea: Decapoda: Pinnotheridae). Proceedings of the Biological Society of Washington, 113, 799 - 805."]}